At the interface of theory and experience - Heller, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2023)
The founding motto of philosophy in science is “tracking down big philosophical problems in contemporary science.” Knowing the basic history of philosophy and the history of science, we more or less know what “big philosophical topics” mean. The most representative topics of this kind include: time, space, causality, matter, life, consciousness, thinking... The tables of contents of philosophy textbooks could be copied to continue this list. These topics are big not only when they remain at a high level of generality, but also when they get down to special cases and particular sub-problems. Sometimes it is only then that they fully reveal their big format.